Common Fixed Point Theorems Using Compatible Mappings of Type (R) in Semi-metric Space - Rajopadhyaya, Umesh; Jha, K. (Mathematics Education Forum Chitwan, 2020)
In this paper, we establish a common fixed point theorem for three pairs of self mappings in semi-metric space using compatible mappings of type (R) which improves and extends similar known results in the literature.